R programming for statistics and data science (Packt Publishing, 2018)
"R Programming is a skill you'll need if you want to work as a data analyst or a data scientist in your industry of choice ... [This course] will get you from a complete beginner in programming with R to a professional who can complete data manipulation on demand. It gives you the complete skillset to tackle any new data science project with confidence and critically assess your work and other people's."--Resource description page